Partisispasi Perempuan dalam Penyelenggara Pemilu Menurut Pandangan Hukum Islam - Supriyadi; Hirmayadi Saputra; Muzakkir S (STIS DAFA MATARAM, 2024)
This study aims to examine women's participation in election administration in Indonesia from the perspective of Islamic law, using a descriptive qualitative method that includes literature review. The results show that women's participation in election administration remains very limited, with the percentage of women in Bawaslu and KPU far below 30%. The main obstacles include patriarchal culture, restrictive interpretations of religious doctrines, and bureaucratic hurdles. Although Islamic law does not explicitly prohibit women's participation, conservative interpretations often limit their roles. This study contributes to the understanding of the dynamics of women's participation in election administration in Indonesia and provides insights for policymakers to design more effective affirmative strategies, highlighting the importance of a gender perspective in equitable election administration.